Two-step protein labeling utilizing lipoic acid ligase and sonogashira cross-coupling - Hauke, Sebastian; Best, Marcel; Schmidt, Tobias Thomas; Baalmann, Mathis; Krause, André; Wombacher, Richard (Bioconjugate chemistry, 2014)
Labeling proteins in their natural settings with fluorescent proteins or protein tags often leads to problems. Despite the high specificity, these methods influence the natural functions due to the rather large size of the proteins used. Here we present a two-step labeling procedure for the attachment of various fluorescent probes to a small peptide sequence (13 amino acids) using enzyme-mediated peptide labeling in combination with palladium-catalyzed Sonogashira cross-coupling. We identified p-iodophenyl derivatives from a small library that can be covalently attached to a lysine residue within a specific 13-amino-acid peptide sequence by Escherichia coli lipoic acid ligase A (LplA). The derivatization with p-iodophenyl subsequently served as a reactive handle for bioorthogonal transition metal-catalyzed Sonogashira cross-coupling with alkyne-functionalized fluorophores on both the peptide as well as on the protein level. Our two-step labeling strategy combines high selectivity of enzyme-mediated labeling with the chemoselectivity of palladium-catalyzed Sonogashira cross-coupling.
Gesehen am 04.09.2020